EssH Peptidoglycan Hydrolase Enables Staphylococcus aureus Type VII Secretion across the Bacterial Cell Wall Envelope - Bobrovskyy, Maksym (J Bacteriol, 2018)
The ESAT-6-like secretion system (ESS) of Staphylococcus aureus is assembled in the bacterial membrane from core components that promote the secretion of WXG-like proteins (EsxA, EsxB, EsxC, and EsxD) and the EssD effector. Genes encoding the ESS secretion machinery components, effector, and WXG-like proteins are located in the ess locus. Here, we identify essH, a heretofore uncharacterized gene of the ess locus, whose product is secreted via an N-terminal signal peptide into the extracellular medium of staphylococcal cultures. EssH exhibits two peptidoglycan hydrolase activities, cleaving the pentaglycine cross bridge and the amide bond of N-acetylmuramyl-l-alanine, thereby separating glycan chains and wall peptides with cleaved cross bridges. Unlike other peptidoglycan hydrolases, EssH does not promote the lysis of staphylococci. EssH residues Cys(199) and His(254), which are conserved in other CHAP domain enzymes, are required for peptidoglycan hydrolase activity and for S. aureus ESS secretion. These data suggest that EssH and its murein hydrolase activity are required for protein secretion by the ESS pathway. IMPORTANCE Gene clusters encoding WXG-like proteins and FtsK/SpoIIIE-like P loop ATPases in Firmicutes encode type 7b secretion systems (T7bSS) for the transport of select protein substrates. The Staphylococcus aureus T7bSS assembles in the bacterial membrane and promotes the secretion of WXG-like proteins and effectors. The mechanisms whereby staphylococci extend the T7SS across the bacterial cell wall envelope are not known. Here, we show that staphylococci secrete EssH to cleave their peptidoglycan, thereby enabling T7bSS transport of proteins across the bacterial cell wall envelope.